Simple Downflow Water Filtration System in Sasake Village - Heri Sulistiyono; Anid Supriyadi; Yusron Saadi; Pathurahman; Akmaluddin; Hardi Pratomo (Unram Journal of Community Service, 2025)
The availability of clean water needs to be a special concern in the community, because there are several cases in various regions in Indonesia where the availability of clean water sources becomes difficult to obtain during the long dry season, one of which is in the West Nusa Tenggara region, specifically in Sasake Village, Praya Tengah District, Central Lombok Regency. The main water source used in Sasake Village is PDAM water. However, in recent years, several villages in Central Lombok Regency have experienced drought, making it difficult to obtain clean water. The BPBD of Central Lombok Regency must prepare clean water at the peak of the dry season for several villages, including Sasake Village. Alternative water sources in Sasake Village are wells and the Batujai Reservoir. However, at the peak of the dry season, the water in several wells becomes cloudy and smelly, so residents cannot use it as clean water. This community service initiative seeks to implement a user-friendly downflow water filtration system designed for community-level ownership, operation, and maintenance. The design of this filter uses a 4" PVC pipe containing filter media, including sand, palm fiber, charcoal (activated carbon), and cotton. This physical water purification process excludes chemical and biological reactions, relying instead on gravity-driven separation of suspended solids from the fluid phase. Based on the filtering results, it is known that this tool can reduce turbidity concentration by 69.3% and eliminate odors. According to the evaluation results of the counseling participants, there has been a significant increase in understanding of simple water filtration methods. Counseling regarding this water filtration tool is crucial so that the community can overcome clean water problems independently.